Wieczna krucjata. Szkice o Don Kichocie - Redakcja (Wydawnictwo Naukowe UAM, 2016)
The monograph Wieczna krucjata [The Eternal Wandering] outlines the wider historical and literary context, allowing Cervantes’ work to be presented against the backdrop of turbulent historical events, and offers a multidimensional look at selected perspectives of authors representing the many disciplines of the humanities. The 400th anniversary of the publication of Don Quixote and death of its author provide a good pretext to reread Miguel Cervantes’ masterpiece and ponder its place in contemporary cultural space. This is a pioneering publication of its type in this field in Polish. The fleeting mosaic of contextualised readings emerging from the twelve sketches that comprise this book testifies to the unremitting ability of Cervantes’ work to inspire. It also provides a useful complement to the invari ably relevant re-readings of the adventures of this inventive knight.

Okrągłe rocznice publikacji „Don Kichota” i śmierci jego autora to dobry pretekst, aby ponownie – czterysta lat później – przeczytać arcypowieść Miguela Cervantesa i zastanowić się nad jej miejscem w powszechnej przestrzeni kulturowej. Niniejsza monografia proponuje wielowymiarowe spojrzenie uwzględniające wybrane perspektywy poszczególnych autorów, reprezentujących rozmaite dyscypliny nauk humanistycznych. Wyłaniająca się z dwunastu pomieszczonych w zbiorze szkiców migawkowa mozaika kontekstualizujących odczytań jest świadectwem niesłabnącej inspiracyjności dzieła Cervantesa i stanowi użyteczne uzupełnienie niezmiennie aktualnej relektury przygód przemyślnego rycerza.
The Eternal Wandering: Sketches on Don Quixote
Keywords: Cervantes; Don Kichot; szkice krytyczne; komparatystyka literacka